2021
DOI: 10.1016/j.hpb.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Axial slicing versus bivalving in the pathological examination of pancreatoduodenectomy specimens (APOLLO): a multicentre randomized controlled trial

Abstract: Background: In pancreatoduodenectomy specimens, dissection method may affect the assessment of primary tumour origin (i.e. pancreatic, distal bile duct or ampullary adenocarcinoma), which is primarily determined macroscopically. This is the first study to prospectively compare the two commonly used techniques, i.e. axial slicing and bivalving.Methods: In four centres, a randomized controlled trial was performed in specimens of patients with a suspected (pre)malignant tumour in the pancreatic head. Primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…In the current study, the median number of 15 retrieved lymph nodes was similar to the 16 nodes retrieved in a recent Dutch multicenter randomized trial on PD specimen grossing 55 . Although this median number of 15 lymph nodes is 54 somewhat below a recent international benchmark cutoff (>16 nodes) 56 it is much lower than >28 required lymph nodes reported in a recent study 57 . The rate of R0 resection (>0 mm definition) was 81% in the current study, which conforms to textbook outcomes for pancreatic adenocarcinoma as identified from the National Cancer Database (>77.9%) 58 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the current study, the median number of 15 retrieved lymph nodes was similar to the 16 nodes retrieved in a recent Dutch multicenter randomized trial on PD specimen grossing 55 . Although this median number of 15 lymph nodes is 54 somewhat below a recent international benchmark cutoff (>16 nodes) 56 it is much lower than >28 required lymph nodes reported in a recent study 57 . The rate of R0 resection (>0 mm definition) was 81% in the current study, which conforms to textbook outcomes for pancreatic adenocarcinoma as identified from the National Cancer Database (>77.9%) 58 .…”
Section: Discussionsupporting
confidence: 80%
“…It is therefore likely that the progression of the experience came with a mitigation of the severity of the complications. During the LAELAPS-3 program, the Dutch PORSCH trial investigated whether the implementation of an algorithm for early detection and management of pancreatic fistula may improve outcomes after pancreatic resection and subsequently halved mortality after pancreatic surgery 54 . This intervention might have increased rate of postoperative fistula, due to increased use of percutaneous drainage, but may also have played a role in the decrease in grade C POPF to 0% after the “mastery” cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…The working group agreed that both bivalving and axial sectioning approach may be used at the preference of the pathologist for pancreaticoduodenectomy specimens resected for PDAC after neoadjuvant therapy. Evolving literature indicates that both approaches provide comparable results, with their respective advantages and disadvantages 40. A multi-institutional, prospective study to compare the bivalving and axial sectioning approaches for pancreaticoduodenectomy specimens in the setting of neoadjuvant treatment is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Evolving literature indicates that both approaches provide comparable results, with their respective advantages and disadvantages. 40 A multi-institutional, prospective study to compare the bivalving and axial sectioning approaches for pancreaticoduodenectomy specimens in the setting of neoadjuvant treatment is currently ongoing. Tumor size measurement is extremely difficult for PDAC after neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the insignificant impact of the kind of pathological evaluation in terms of R1 rate reported in our study confirmed that reported by a recent randomized controlled trial published by the Dutch Pancreatic Cancer Group. In this study, bivalve and axial slicing of PD specimen were evaluated: the R1 rate was similar with the two slicing techniques (60% and 55%, respectively; p = 0.71) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%